The influence of Gross Regional Domestic Product (GRDP) and regional spending on regional original income Period 2010 - 2019 in DKI Jakarta Province - Zaenal Arifin (Monas: Jurnal Inovasi Aparatur, 2022)
Increasing Regional Original Income (PAD) is one of the success factors in achieving regional development goals. This is because PAD determines the capacity of local governments to carry out government functions, namely public services (public service functions) and development (development functions). This study reveals how much influence GRDP and Regional Expenditures have on Regional Original Income in DKI Jakarta Province for the 2010-2019 period. This study uses secondary data from the Regional Financial Management Agency (BPKD) and BPS with nine periods, namely from 2010-to 2019; the survey was conducted from September-November 2021. The data was analyzed using the OLS method (Eviews-10) with the data processing method, namely Multiple Linear Regression Analysis. The results of this study indicate that: (1) GRDP has a positive and significant effect on local revenue in DKI Jakarta Province for the 2010-2019 period. (2) Regional Expenditures have a positive and insignificant effect on Regional Original Income of DKI Jakarta Province for the 2010-2019 Period (3) Simultaneously, GRDP and Regional Expenditures have a significant and influential effect on Regional Original Income of DKI Jakarta Province for the 2010-2019 period.